2013
DOI: 10.4236/ns.2013.55a003
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive alternatives for DNA collection from threatened rodents

Abstract: Many rodent species are currently under conservation threat. However, population monitoring and status assessment are extremely challenging because of small body size, low abundance and elusive behavior of rodents. Furthermore, invasive methods of capture and tissue collection commonly used to address such studies can induce an unacceptable amount of stress to sensitive species. As a result, noninvasive techniques have become more widely used, but relatively few studies have applied noninvasive techniques to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Studies on rodent populations are often difficult to perform due to their nocturnal activity (Green et al 2013). Direct observations at night are inefficient, and live-trapping is an expensive and time-consuming process (Alasaad et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on rodent populations are often difficult to perform due to their nocturnal activity (Green et al 2013). Direct observations at night are inefficient, and live-trapping is an expensive and time-consuming process (Alasaad et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested the use of fecal matter more promising in comparison to the traditional DNA sources whose collection and use is quite difficult. While there is no tissue that can universally be applied to all research projects, fecal matter is a much more promising alternative to traditional invasive procedures which can be applied to study any species under threat [30] . In accordance to this, this study is a pioneer attempt on reptiles to use fecal pellets as source of DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Small rodents are prevalent in ecosystems across the globe, with many species acting as ecosystem engineers (Dickman, 1999) or keystone species (Ims & Fuglei, 2005); with numerous rare species of high conservation value (Green, Ting, Manjerovic, & Mateus-Pinilla, 2013) and many invasive populations with profound effects on ecosystem functioning (Dickman, 1999). Monitoring and research of small rodents is thus a globally salient enterprise for ecosystem management, conservation, forestry and agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring and research of small rodents is thus a globally salient enterprise for ecosystem management, conservation, forestry and agriculture. Yet, obtaining population- or community-level data on small rodents is often challenging, as these small and cryptic animals are elusive (Green et al, 2013) and cost-effective methods for large-scale sampling of their multispecies communities are largely missing (Engeman & Whisson, 2006; Heisler, Somers, & Poulin, 2016). State-of-the-art estimation of small rodent community composition, population size and density, relies on a variety of trapping and indexing efforts, e,g, pitfalls, live-, snap-, hair- or camera traps and systematic incidental observations (Engeman & Whisson, 2006; Soininen, Jensvoll, Killengreen, & Ims, 2015; Fauteux et al, 2018), or on counts of burrows, runways, winter nests, owl pellet contents and faeces (Green et al, 2013; Heisler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%